Technologies for deposition of transition metal oxide thin films: application as functional layers in "Smart windows" and photocatalytic systems. (January 2016) - Gesheva, K; Ivanova, T; Bodurov, G; Szilágyi, I M; Justh, N; Kéri, O; Boyadjiev, S; Nagy, D; Aleksandrova, M
Abstract: "Smart windows" are envisaged for future low-energy, high-efficient architectural buildings, as well as for the car industry. By switching from coloured to fully bleached state, these windows regulate the energy of solar flux entering the interior. Functional layers in these devices are the transition metals oxides. The materials (transitional metal oxides) used in smart windows can be also applied as photoelectrodes in water splitting photocells for hydrogen production or as photocatalytic materials for self-cleaning surfaces, waste water treatment and pollution removal. Solar energy utilization is recently in the main scope of numerous world research laboratories and energy organizations, working on protection against conventional fuel exhaustion. The paper presents results from research on transition metal oxide thin films, fabricated by different methods - atomic layer deposition, atmospheric pressure chemical vapour deposition, physical vapour deposition, and wet chemical methods, suitable for flowthrough production process. The lower price of the chemical deposition processes is especially important when the method is related to large-scale glazing applications. Conclusions are derived about which processes are recently considered as most prospective, related to electrochromic materials and devices manufacturing.